Identification des bactéries lactiques à propriétés probiotiques et technologiques isolés à partir de différents laits fermentés - BENSMAINE, SORIA HAFSA; HAMMOU, YAMINA (My University, 2023)
In this study, seven lactic strains were isolated from two origins (traditional butter, goat's milk). After isolation, the strains were characterized and identified by morphological, physiological and biochemical tests to identify the genus and then tested for their technological aptitudes: aromatic and proteolytic activity, the ability to produce exopolysaccharides (EPS), and their probiotic properties: power antibacterial against pathogenic bacteria: E.coli ATCC 2592, S.aureu ATCC 2593 and resistance to antibiotics. The results obtained indicate that certain strains have technological aptitudes and interesting probiotic characters: the production of exopolysaccharides (EPS), flavoring power, significant proteolytic power with an inhibitory power against the pathogenic germs used, and very good resistance to antibiotics.
Keywords: proteolytic activity; antibiotic resistance; Lactococcus; Lactobacillus; EPS; antibacterial activity